Penyusunan dan Pengembangan Alat Ukur Employee Engagement - Titien Titien (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2016)
Abstract: This research was aimed to develop an instrument which can measure employee engagement score, which is based on Schaufeli’s theoretical framework. The previous instrument which was called Utretch Work Engagement Scale (UWES) was developed using content and construct validity. The content validity test was done by assessing some experts and using Aiken’s V, while construct validity was proved by item total correlation and factor analysis. Content validity test was conducted by getting input from fifteen experts in Psychology to evaluate the contents of 32 items. The Aiken’s V was used to evaluate the coefficient of each items (in which good range was from 0,645 to 0,98). The overall internal consistency was assessed using Cronbach alpha which showed the coefficient of reliability of 0,934 after deleting the items below 0,4, whereby leaving only 22 items for conducting the construct validity. Confirmatory factor analysis was done using factor analysis. 135 staffs in one of Plantation Company in Balikpapan were participated in this study. The confirmatory factor analyses produced a cross loading factors between three aspects of employee engagement which after confirming back to blueprint remaining only 8 items, which is distributed into 4 items for vigor, 2 items each for dedication and absorption.Abstrak: Penelitian ini bertujuan untuk mengembangkan instrumen yang dapat mengukur skor employee engagement yang didasarkan pada kerangka teoritis yang dikemukakan oleh Schaufeli. Instrumen sebelumnya dikenal dengan Utretch Work Engagement Scale (UWES) yang dikembangkan dengan menggunakan validitas isi dan konstrak. Validitas isi diuji melalui judgment dari para ahli di bidang Psikologi dan menggunakan Aiken’s V, sedangkan validitas konstrak dibuktikan dengan korelasi item-total dan analisis faktor. Validitas isi diperoleh dari 15 orang yang ahli di bidang Psikologi untuk mengevaluasi isi dari 32 item. Aiken’s V digunakan untuk mengevaluasi koefisien dari setiap item (range yang baik berada di rentang 0,645 sampai 0,98). Konsistensi internal diperoleh melalui alpha Cronbach dengan koefisien reliabilitas sebesar 0,934 setelah item-item yang memiliki nilai di bawah 0,4 dikeluarkan. Total item yang tersisa berjumlah 22 item untuk kemudian dilakukan uji validitas konstrak. Confirmatory factor analysis dilakukan melalui analisis factor. Sebanyak 135 staf di salah satu Perusahaan Plantation di Balikpapan berpartisipasi dalam penelitian ini. Hasil analisis factor menunjukkan adanya factor yang saling tumpang tindih antara ketiga aspek dari employee engagement, yang setelah dikonfirmasi kembali ke blueprint menyisakan sebanyak 8 item, 4 item untuk aspek vigor, 2 item masing-masing untuk aspek dedication dan absorption.